THE ROLE OF CASH HOLDING, CORPORATE SOCIAL RESPONSIBILITY AND OPERATING CAPACITY ON FINANCIAL DISTRESS WITH CASH FLOW AS A MODERATING VARIABLE - Rahmawati, Ulva Amalia; Setiawan, Ananda (Jurnal Akuntansi dan Keuangan (JAK), 2025)
The purpose of this study is to determine and analyze the influence of cash holding, corporate social responsibility and operating capacity on financial distress with cash flow as a moderating variable. The subject of this study is manufacturing companies listed in the Indonesian Sharia stock index for the period 2020 to 2023. The data collection method uses a purposive sampling technique, so that a sample of 35 companies was obtained with a total of 140 studies. This study uses secondary data with a quantitative approach and the data is analyzed by Moderated Regression Analysis (MRA) with the help of Eviews software version 12. The theoretical basis used in this study is Signaling Theory. The results showed that cash holding had a significant negative effect on financial distress, while corporate social responsiveness and operating capacity did not have a significant effect on financial distress. Then, the results of the study also show that cash flow as a moderation variable is able to strengthen the influence of cash holding on financial distress. Cash flow as a moderation variable is not able to strengthen the influence of corporate social responsiveness on financial distress. Cash flow as a moderation variable is not able to strengthen the influence of operating capacity on financial distress.